The Effecttiveness of topical cyclosporine 0.05% compared to topical fluorometholone 0.1% in the therapy of vernal keratoconjunctivitis - Agus Supartono, Edy Ariston Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Vernal keratoconjunctivitis (VKCI is a chronic and often severe form of bilateral tarsal and or bulbar conjunctivitis. Several studies have reported that topical corticosteroid therapy was effective and cyclosporine was very effective in the treatment of moderate and severe VKC. In this study we wanted to know the effectiveness of topical cyclosporine 0.05% compared to topical fluorometholone 0.1 % in VKCObjective: The objective of this research was to know the effectiveness and side effect on the raise of intraocular pressure of 0.05% cyclosporine eyedrop compared 0.1 % fluorometholone on patients suffered from vernal keratoconjunctivitisMethods: A double blind randomized controlled trial was performed on the subjects suffered from vernal keratoconjunctivitis who fulfilled inclusion and exclusion criteria. The subjects were allocated into two groups by block randomization. The first group was given 0.05% cyclosporine eye drops, whereas on the other group was given 0.1 % fluorometholone eye drop. All the subjects were examined for the clinical symptoms and signs, intraocular pressure, eosinophil count with Giemsa staining before and one month after treatment. The cyclosporine group consisted of 21 subjects whereas the 0.1 % fluorometholone group was 22 subjects. The ages of both groups were within the age range of 4-36 years old.Results: Both groups showed improvement of symptoms and signs and were not statistically significant difference (p = 0.311; 95% CI: 0.102-0.3131. xxxx The use of 0.1% fluorometholone eyedrops for one month was not associated with any increase of lOP compared to 0.05% cyclosporine (p = 0.11 and p = 0.12). There was improvement in the eosinophil count in both groups and no statistical significant difference (p = 0.301. The side effect of pain was more in 0.05% cyclosporine administration and the difference was statistically significant (p=0.0011 with number needed to harm (NNHI of 2.69.Conclusion: It was concluded that the use of 0.05% cyclosporine eyedrop was as effective as the use of 0.1 % fluorometholone but the side effect of pain occured more often. No statistical difference was found between either the intraocular pressure increase or the eosinophil count in the use of 0.05% cyclosporine eyedrop compared to 0.1 % fluorometholone.Keywords: Vernal keratoconjunctivitis - cyclosporine 0.05% - fluorometholone 0.1 % - side effects, eosinophilÂ count